Tax Competition : Is It a Source of the Corporate Savings Glut? - Kawamoto, Atsushi; Muraki, Kei (World Bank, Washington, DC, 2020)
This paper examines the determinants of corporate savings in a cross-country panel setting. Specifically, it employs firm-level data covering more than 540,000 firm-year observations for 12 advanced and emerging market economies. Panel regression results suggest that reductions in statutory corporate income tax rates can explain one-third of the rise in corporate savings (defined as net financial assets) in 2003-17. This finding is supported by a propensity scores matching analysis of the effects of changes in corporate income tax rates.